The Influence of Service Quality and Employe Competence on Community Satisfaction at The Tebing Tinggi Sub-District Office, Balangan Regency - Oktavianty, Puteri Anggraini; Jumaidi , Jumaidi; Hidayatullah , Gusti Muhammad (International Journal on Economics, Finance and Sustainable Development, 2025)
The problems that occur in relation to the Effect of Service Quality and Employee Competence on Community Satisfaction at the Tebing Tinggi District Office, Balangan Regency are the skills and knowledge of service officers who are still uneven, the  turnaround time is not on time, the response of officers is still low and service information is lacking. complete. The purpose of this study was to determine the effect of service quality and employee competence on community satisfaction at the Tebing Tinggi District Office, Balangan Regency partially and simultaneously and the magnitude of the effect. The type of research used is quantitative research methods with data collection techniques of questionnaires, observations and documentation, and using incidental sampling techniques for determining samples, data analysis methods include Editing, Codeting, and Tabulation activities which are then assisted by statistical data processing applications namely IBM SPSS 26.0 Statistics For Windows. The results of the study indicate that there is a positive and significant influence between Service Quality, Competence on Community Satisfaction at the Tebing Tinggi District Office, Balangan Regency. This is evidenced by the results of Fcount = 24.140, the value of Fcount will be compared with Ftable. The value of Ftable with dfreg = 1 and dfres = 53 is 4.00 at the 5% level, then the regression coefficient value for the variable Quality of Service is 0.429, and is significant 0.000 <0.05, Competence is 0.152 and is significant 0.001 <0.05, this means that the variables of Service Quality and Competence have a positive and significant influence on Community Satisfaction. The great influence of service quality and competency on community satisfaction at the Tebing Tinggi District Office, Balangan Regency, namely partially, service quality, based on the R Square value of service quality is 0.459 or 45.9%, so it can be said that the Service Quality Variable has an effect of 45.9% on Community Satisfaction, Competence, based on the Competency R Square value of 0.169 or 16.9%, it can be said that the Competency Variable has an effect of 16.9% on Community Satisfaction. Simultaneously Based on the value of R2 (R Square) or a coefficient of determination of 0.486 or 48.6%. This shows that the percentage of contributions to the influence of the Quality of Service variable on the Community Satisfaction variable at the Tebing Tinggi District Office, Balangan Regency is 48.6%, while the remaining 31.4% is influenced and explained by other variables not included in this research model. Based on the results of research and discussion, suggestions that can be explored is that the Head of Tebing Tinggi Subdistrict, Balangan Regency should be more active in providing work supervision, Employees should improve work discipline and Further Researchers add variables other than Service Quality which are thought to affect Community Satisfaction.